2017
DOI: 10.1128/mbio.02336-16
|View full text |Cite
|
Sign up to set email alerts
|

Density-Dependent Recycling Promotes the Long-Term Survival of Bacterial Populations during Periods of Starvation

Abstract: The amount of natural resources in the Earth’s environment is in flux, which can trigger catastrophic collapses of ecosystems. How populations survive under nutrient-poor conditions is a central question in ecology. Curiously, some bacteria persist for a long time in nutrient-poor environments. Although this survival may be accomplished through cell death and the recycling of dead cells, the importance of these processes and the mechanisms underlying the survival of the populations have not been quantitated. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 48 publications
(52 reference statements)
1
60
0
1
Order By: Relevance
“…The rpoS819 mediated GASP has been directly correlated with enhanced ability to scavenge amino acids, the key nutrients released by dead cells. This can be modulated by altering environmental factors such as pH of the medium (11,15,52). Strong selection for rpoS92, which partially recovers RpoS activity, indicates further tuning of RpoS activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rpoS819 mediated GASP has been directly correlated with enhanced ability to scavenge amino acids, the key nutrients released by dead cells. This can be modulated by altering environmental factors such as pH of the medium (11,15,52). Strong selection for rpoS92, which partially recovers RpoS activity, indicates further tuning of RpoS activity.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli survival during prolonged stationary-phase is illustrated by the phenomenon of Growth Advantage in Stationary-Phase (GASP). During GASP, genetic variants called GASP mutants arise and proliferate in the primarily non-growth environment of prolonged stationary-phase, presumably by extracting nutrients from dead cell debris (10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…But the exact same questions remain to be elucidated in this field: how many cell divisions happen in these starving colonies? In batch cultures, is stationary phase really stationary, or is there some turnover and recycling as recently suggested [48]? And more importantly, where does death come from: is it an unavoidable, externally caused phenomenon; or is there an internal component, such as an altruistic programmed cell death [50], or just traits selected in other environments that give a maladaptation to certain stresses [23]?…”
Section: Discussionmentioning
confidence: 99%
“…However, the study unfortunately failed to remove the dead cells in the long‐term stationary phase. A recent study showed that nutrients in the culture are supplied from the dead cells who exist in large numbers, and the bacterial growth was restricted by cell‐to‐cell interactions before the exhaustion of nutrients in such conditions (Takano et al, ). These new findings suggest unclearness or complexity of selective pressure in the long‐term stationary phase.…”
Section: Discussionmentioning
confidence: 99%
“…However, this evolution experiment consists of very complicated selections during extensive death phase and long‐term stationary phase. For instance, our recent study found that the resources are not limited in the long‐term stationary phase due to leakage from dead cells (Takano, Pawlowska, Gudelj, Yomo, & Tsuru, ), implying that selections act on the other traits rather than histidine utilization. Thus, it is still unknown whether the mutations improving carrying capacity in histidine utilization are pervasive or not.…”
Section: Introductionmentioning
confidence: 99%